Effectiveness and Strategies for Addressing Hotel Tax Problems in Baubau City - Abidin, Zainul (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effectiveness of hotel taxes and analyze strategies to increase them in Indonesia, specifically in Baubau City, using a mixed research design with a sequential explanatory strategy. To assess the impact of hotel tax effectiveness on Local Own Revenue (Pendapatan Asli Daerah, PAD) in Baubau City, the study utilized a quantitative approach with a correlation-based survey. Data were analyzed using descriptive techniques and an interactive model. The findings indicate that from 2018 to 2020, there was only a 2.52% increase in Baubau City’s PAD attributable to hotel tax effectiveness. The tax increase strategies, including both intensification and extensification implemented by the Asset and Revenue Management Agency of Baubau City, exhibited several weaknesses, leading to numerous challenges in tax enhancement efforts. Despite the COVID-19 pandemic, no strategic changes were made to increase hotel tax revenues. The implications suggest that future improvements should focus on optimizing strategies of intensification and extensification, incorporating innovations and the use of developing digitalization instruments to boost hotel tax contributions and Local Own Revenue in Baubau City. Effective strategy optimization is essential for enhancing the impact of hotel tax effectiveness.